Innovators in Chile need to be the local heroes: Interview with Tina Seelig - Contreras, Paulina (Base Diseño e Innovación, 2014)
The author of “ingenius, a crash course on creativity”, speaks from silicon valley to say that everybody can stimulate innovation, and also that local innovators need to be recognized as “role models”.